2015
DOI: 10.1371/journal.pone.0138202
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Technical Variant Liver Transplantation versus Whole Liver Transplantation for Pediatric Patients: A Meta-Analysis

Abstract: ObjectiveTo overcome the shortage of appropriate-sized whole liver grafts for children, technical variant liver transplantation has been practiced for decades. We perform a meta-analysis to compare the survival rates and incidence of surgical complications between pediatric whole liver transplantation and technical variant liver transplantation.MethodsTo identify relevant studies up to January 2014, we searched PubMed/Medline, Embase, and Cochrane library databases. The primary outcomes measured were patient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 51 publications
(27 reference statements)
5
14
1
Order By: Relevance
“…The SPLIT group also found that reoperation within 30 d was more common in split, reduced and living donor grafts (which accounted for 77% of our grafts)[ 14 ], and that 30-d survival was 93%, again comparable to our findings[ 14 ]. A recent meta-analysis found that 1-year pediatric patient and graft survival for whole liver grafts was 91% and 84.9%, and for technical variant grafts 87.7% and 77.2% respectively, comparable to our 6-mo patient and graft survivals of 89% and 78%[ 15 ].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The SPLIT group also found that reoperation within 30 d was more common in split, reduced and living donor grafts (which accounted for 77% of our grafts)[ 14 ], and that 30-d survival was 93%, again comparable to our findings[ 14 ]. A recent meta-analysis found that 1-year pediatric patient and graft survival for whole liver grafts was 91% and 84.9%, and for technical variant grafts 87.7% and 77.2% respectively, comparable to our 6-mo patient and graft survivals of 89% and 78%[ 15 ].…”
Section: Discussionsupporting
confidence: 82%
“…The rates of HAT, PVT, and bile leak were higher than in most reports. For example, HAT is often in the range of 5%-10% (compared to our rate of 19%)[ 2 , 8 , 11 , 14 , 15 , 17 , 18 , 22 - 27 ], PVT in the range of 5%-15% (compared to our rate of 17%)[ 2 , 11 , 15 - 18 , 24 - 26 , 28 , 29 ], and bile leak in the range of 2%-15% (compared to our rate of 23%)[ 10 , 15 , 16 , 26 , 29 ]. A report from the SPLIT database found high rates of vascular complications (25%), PVT (16%), and bile leak (21%) in the 6.7% of recipients with complex vascular anomalies[ 30 ]; however, we did not find an association of abnormal anatomy comments and thrombosis or severe complications.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…OLT is the last treatment option for ESLD. Since the first OLT was performed, substantial progress has been achieved in the overall survival, with a 1‐year survival rate of approximately 30% in the 1970s to a current rate of 90% and a 5‐year survival rate exceeding 70% . In the pediatric population, the indications for OLT are divided into chronic liver disease and acute liver failure.…”
Section: Introductionmentioning
confidence: 99%
“…-onset patients (78%, 7/9) had an abnormal ultrasound at the time of diagnosis of NRH. During their clinical follow-up, 60 biopsies were performed in the 17 patients, with a median of 3.6 (1-8) and 3.4(1)(2)(3)(4)(5)(6)(7)(8) biopsies performed in the early-and late-onset presentation groups, respectively. In one case, the graft type of transplanted was not available.…”
mentioning
confidence: 99%